Laboratory Testing for Tick-Borne Infections in a Large Northeastern Academic Medical Center: An 11-Year Experience. Issue 5 (19th July 2018) - Rudolf, Joseph; Baron, Jason; Branda, John; Lee-Lewandrowski, Elizabeth
Abstract: Objectives: We evaluated changes in the testing menu, volume, and positivity rates for tick-borne illnesses in a New England medical center over an 11-year time frame. Methods: Testing data were obtained by a retrospective review utilizing searchable data from a laboratory information system archive. Results: Testing for tick-borne infections (TBI) increased 5.3-fold over an 11-year time period and the number of positive test results increased threefold. Annual rates for Lyme serology positivity varied from 14% to 29% and for western blot confirmation from 26% to 48%. Test volumes and the number of positive results increased for all TBI endemic to our region. Conclusions: Our results confirm national trends suggesting increasing rates of TBI and substantially increased testing. This may reflect a greater incidence of TBI in our region and/or increased awareness of these infections.